KRITIK MATAN DAN URGENSINYA DALAM PEMBELAJARAN HADIS: - Alvida, Alvidatuz; Shilviana, Khusna Farida (Al-Bukhari : Jurnal Ilmu Hadis, 2020)
Disputes among hadiths are a long lasting issue both for Muslims and outsiders who try to mislead the traditionas and create catastrophe in the community.Therefore,it is essential to understad the degree of a hadith more comprehensively, especially in hadiths learning processes. This research is a respond toward the critique of prophetic traditions and its urgency in learning. In this research , I will explore the matan of a hadith on the Prophet David fasting respectively. This research is a library research based on the textuals matan criticism found in the Islamic historical heritages. The results of this study are notes on how the application of matan criticism that occurred in the pre and post-codification periods as well as the validity method of matan critiques which free from shaz and ?Illat. Also some notes on the urgency of learning the method of matan criticism.